Redox-Coupled Protonation of Respiratory Complex I: The Hydrophilic Domain - Couch, Vernon (The Biophysical Society, 2011)
Respiratory complex I, NADH:ubiquinone oxidoreductase, is a large and complex integral membrane enzyme found in respiring bacteria and mitochondria. It is responsible in part for generating the proton gradient necessary for ATP production. Complex I serves as both a proton pump and an entry point for electrons into the respiratory chain. Although complex I is one of the most important of the respiratory complexes, it is also one of the least understood, with detailed structural information only recently available. In this study, full-finite-difference Poisson-Boltzmann calculations of the protonation state of respiratory complex I in various redox states are presented. Since complex I couples the oxidation and reduction of the NADH/ubiquinone redox couple to proton translocation, the interaction of the protonation and redox states of the enzyme are of the utmost significance. Various aspects of complex I function are presented, including the redox-Bohr effect, intercofactor interactions, and the effects of both the protein dielectric and inclusion of the membrane.